Acute Hepatitis E: Two Sides of the Same Coin - Johannes Hartl; Malte H. Wehmeyer; Sven Pischke (Viruses, 2016)
The relevance of acute hepatitis E virus (HEV) infections has been underestimated for a long time. In the past, HEV infection had been interpreted falsely as a disease limited to the tropics until the relevance of autochthonous HEV infections in the Western world became overt. Due to increased awareness, the incidence of diagnosed autochthonous HEV infections (predominantly genotype 3) in industrialized countries has risen within the last decade. The main source of infections in industrialized countries seems to be infected swine meat, while infections with the tropical HEV genotypes 1 and 2 usually are mainly transmitted fecal-orally by contaminated drinking water. In the vast majority of healthy individuals, acute HEV infection is either clinically silent or takes a benign self-limited course. In patients who develop a symptomatic HEV infection, a short prodromal phase with unspecific symptoms is followed by liver specific symptoms like jaundice, itching, uncoloured stool and darkened urine. Importantly, tropical HEV infections may lead to acute liver failure, especially in pregnant women, while autochthonous HEV infections may lead to acute-on-chronic liver failure in patients with underlying liver diseases. Immunosuppressed individuals, such as transplant recipients or human immunodeficiency virus (HIV)-infected patients, are at risk for developing chronic hepatitis E, which may lead to liver fibrosis and cirrhosis in the long term. Importantly, specific treatment options for hepatitis E are not approved by the regulation authorities, but off-label ribavirin treatment seems to be effective in the treatment of chronic HEV-infection and may reduce the disease severity in patients suffering from acute liver failure.